Implementation of A Reasoned Multiple-Choice Test to Identify Students’ Conceptual Mastery of Static Fluid - Yuliana, Ina; Purnama Heny, Ajeng (Universitas Negeri Padang, 2025)
This study aims to identify students’ conceptual mastery of static fluid concepts through the implementation of a reasoned multiple-choice test. The instrument used in this study was a reasoned multiple-choice test consisting of 15 items. A quantitative descriptive method was employed by analyzing the combinations of students’ answers and their accompanying reasoning, which were then categorized into conceptual mastery, partial understanding, and indications of misconception. The results show that the percentage of students who demonstrate true conceptual mastery is still low, while partial understanding and indications of misconception dominate, particularly in the concepts of hydrostatic pressure, Pascal’s law, and Archimedes’ principle. These findings indicate that many students are unable to provide appropriate scientific reasoning even when they occasionally select the correct answer. Therefore, more targeted instructional strategies and continuous diagnostic assessments are needed to support the improvement and development of stronger conceptual mastery.